Axon terminal hypertrophy of striatal projection neurons with levodopa-induced dyskinesia priming - Nakamura, Takashi; Nishijima, Haruo; Mori, Fumiaki; Kinoshita, Iku; Kon, Tomoya; Suzuki, Chieko; Wakabayashi, Koichi; Tomiyama, Masahiko (Frontiers in Neuroscience, 2023)
Background A rat model of levodopa-induced dyskinesia (LID) showed enlarged axon terminals of striatal direct pathway neurons in the internal segment of the globus pallidus (GPi) with excessive gamma-aminobutyric acid (GABA) storage in them. Massive GABA release to GPi upon levodopa administration determines the emergence of LID. Objectives We examined whether LID and axon terminal hypertrophy gradually develop with repeated levodopa treatment in Parkinsonian rats to examine if the hypertrophy reflects dyskinesia priming. Methods 6-hydroxydopamine-lesioned hemiparkinsonian rats were randomly allocated to receive saline injections (placebo group, 14 days; n = 4), injections of 6 mg/kg levodopa methyl ester combined with 12.5 mg/kg benserazide (levodopa-treated groups, 3-day-treatment; n = 4, 7-day-treatment; n = 4, 14-day-treatment; n = 4), or injections of 6 mg/kg levodopa methyl ester with 12.5 mg/kg benserazide and 1 mg/kg 8-hydroxy-2-(di-n-propylamino)tetralin for 14 days (8-OH-DPAT-treated group; n = 4). We evaluated abnormal involuntary movement (AIM) scores and axon terminals in the GPi. Results The AIM score increased with levodopa treatment, as did the hypertrophy of axon terminals in the GPi, showing an increased number of synaptic vesicles in hypertrophied terminals. Conclusion Increased GABA storage in axon terminals of the direct pathway neurons represents the priming process of LID.